2021
DOI: 10.47672/ajep.869
|View full text |Cite
|
Sign up to set email alerts
|

Digitalizing the Teaching and Learning of Mathematics at the Senior High Schools in Ghana; the Case of Flipped Classroom Approach

Abstract: Introduction: The 21st century comes with its own challenges so far as the teaching and learning of mathematics is concern. This is because most of the senior students have access to digital devices that allow them to navigate the social media channels like the WhatsApp, Twiter, instagram, SnapChat, Facebook, TikTok and the likes. Unfortunately these handles are loaded with various forms of videos and other stuffs that these innocent young ones turned to love to follow more than their studies, thereby affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The develop of technology and the role of it in flipped classroom model to promoting and the growth of online learning environments should be enhanced (Chai & Kong, 2017;Thanh et al, 2021). It is supported by other previous research that found a positive impact on students' activities and learning outcomes at many levels and subjects (Amoako Atta & Brantuo, 2021;Griffin et al, 2012). Besides the goal of introducing a style-based blended teaching-learning model to develop learning competencies in general, and at the same time develop a specific competency for the ability to integrate tools to support learning activities (Asuman et al, 2018;Liang, 2012;Prestiadi et al, 2020).…”
Section: Introductionsupporting
confidence: 78%
“…The develop of technology and the role of it in flipped classroom model to promoting and the growth of online learning environments should be enhanced (Chai & Kong, 2017;Thanh et al, 2021). It is supported by other previous research that found a positive impact on students' activities and learning outcomes at many levels and subjects (Amoako Atta & Brantuo, 2021;Griffin et al, 2012). Besides the goal of introducing a style-based blended teaching-learning model to develop learning competencies in general, and at the same time develop a specific competency for the ability to integrate tools to support learning activities (Asuman et al, 2018;Liang, 2012;Prestiadi et al, 2020).…”
Section: Introductionsupporting
confidence: 78%
“…Students can reach this stage through assistance from other capable individuals or through their efforts through the conceptual change model, i.e., Accommodation and assimilation processes (Belbase et al, 2022;Gómez, 2016). The constructivist education theory implies that students must be challenged to take responsibility for their learning (Atta & Brantuo, 2021). Therefore, the teachers should act as coaches, curators, or facilitators to facilitate students' independent learning (Minarni & Napitupulu, 2020).…”
Section: The Psychomotor Domainmentioning
confidence: 99%
“…Therefore, the teachers should act as coaches, curators, or facilitators to facilitate students' independent learning (Minarni & Napitupulu, 2020). When the student is actively involved in constructing knowledge, it is expected to enhance their chance of utilizing it to solve contextual problems (Atta & Brantuo, 2021).…”
Section: The Psychomotor Domainmentioning
confidence: 99%
“…Second, android games can present learning materials interactively, such as through challenges, puzzles, or real-life simulations, which make the learning process more exciting and fun. Third, android games can also provide students with direct feedback, so they can correct mistakes and increase their understanding of English effectively (Amoako Atta & Brantuo, 2021;Halabi, 2020). This research on the digitalization of teaching materials based on mobile learning android games in the English language for elementary schools aims to explore the effectiveness of this learning method in improving students' English language ability and analyze the positive impact it has on the learning process.…”
Section: Introductionmentioning
confidence: 99%